Os elementos do clima e sua (co) relação com os casos de Covid-19/SARS-CoV-2 em Fortaleza/CE - Lopes, Rebecca Nogueira (2024)
In the last four years, the world has faced the Covid-19/SARS-CoV-2 pandemic. Its rapid spread has sparked debates about the impacts of human activities on the environment and their consequences for health. Efforts have begun to investigate the relationship between climate and cases of the disease, given that the influence of climate on the manifestation of these cases is already recognized. The city of Fortaleza stood out as the national epicenter of the pandemic, with a rapid increase in the number of cases. This study seeks to better understand the interactions between climate and the pandemic situation. With the main objective of analyzing the (co)relationship between notable climate elements in the city of Fortaleza/CE and cases of Covid-19/SARS-CoV-2, the following study will work with qualitative and quantitative analyses, considering that a pandemic permeates all aspects of a society. For the quantitative analysis, the research will rely on Spearman's Correlation statistics, the objective of which is to determine the degree of correlation between the two variables. The determination of the coefficients will be done using the R Software. In the qualitative aspect, the Rhythmic Analysis technique will be adopted, using data in chronological decomposition to assess the Climatic Rhythm, covering the analysis of the active atmospheric systems, air masses and the determination of weather types. For this purpose, synoptic charts and satellite images will be used. As a result of the application of statistical and climatological techniques, the levels of correlation between all climate elements in relation to the number of Covid-19 cases between 2020 and 2023 will be determined. In addition, graphs from the application of the Rhythmic Analysis technique will be produced. It is considered, in advance, that a pandemic scenario has unique complexity in any study to be carried out. The number of variables uncommon to climate study is comprehensive. Knowing this fact, the results obtained through the adopted procedures point to the existence of a significant (co)relationship between the climate elements studied and the cases of the disease, especially wind speed. It is also possible to associate the predominant climatic elements with the dynamics established by the entry of variants and subvariants during the course of the pandemic in the city. The conclusions drawn reinforce the need to integrate Climatology and Health studies with the health policies adopted for societies, especially considering their climatic particularities and the growing interaction between societies and the Climate at different scales.